2021
DOI: 10.21203/rs.3.rs-316316/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The clinical significance of preoperative serum fibrinogen levels and platelet counts in patients with Gallbladder carcinoma

Abstract: Background: Gallbladder carcinoma (GBC) was the most common malignancy of biliary tract. Patients with malignancies frequently present with activated coagulation pathways, which mightpotentially related to tumor progression and prognosis. The purpose of the study was to investigate the clinical significance of preoperative serum fibrinogen levels and platelet counts in GBC patients.Methods: The preoperative fasting serum fibrinogen levels and platelet counts of 58 patients with GBC were measured by AUV2700 aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…studies have indicated that preoperative brinogen was closely associated with the long-term prognosis of patients with GBC, which has been regarded as a prognostic factor (4,(12)(13)(14). The observations reported in other studies have also been validated in our cohort as well as the subsequent meta-analysis that an elevated preoperative brinogen indicated a more advanced tumor stage and a much worse prognosis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…studies have indicated that preoperative brinogen was closely associated with the long-term prognosis of patients with GBC, which has been regarded as a prognostic factor (4,(12)(13)(14). The observations reported in other studies have also been validated in our cohort as well as the subsequent meta-analysis that an elevated preoperative brinogen indicated a more advanced tumor stage and a much worse prognosis.…”
Section: Discussionsupporting
confidence: 82%
“…Accumulating evidence has revealed the co-existence of cancer-derived coagulation abnormalities and demonstrated the prognostic value of the coagulation-related medium, especially brinogen, in various human malignancies, such as peri-hilar cholangiocarcinoma (9), colorectal carcinoma (10), and pancreatic carcinoma (11). The prognostic role of preoperative brinogen in patients with GBC has also been deeply explored (4,(12)(13)(14). CA199 has always been regarded the most commonly used and gold-standard tumor biomarker in patients with biliary cancers (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%